2020
DOI: 10.1101/2020.02.14.950006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parvalbumin+and Npas1+Pallidal Neurons Have Distinct Circuit Topology and Function

Abstract: The external globus pallidus (GPe) is a critical node within the basal ganglia circuit. Phasic changes in the activity of GPe neurons during movement and their alterations in Parkinson’s disease (PD) argue that the GPe is important in motor control. PV+ neurons and Npas1+ neurons are the two principal neuron classes in the GPe. The distinct electrophysiological properties and axonal projection patterns argue that these two neuron classes serve different roles in regulating motor output. However, the causal rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 172 publications
7
29
1
Order By: Relevance
“…The STN is reciprocally connected to the GPe and has been considered to be the main source of excitatory input to the GPe (Kita et al, 1983; Kita and Kitai, 1991; Pamukcu et al, 2020). To study the STN inputs to GPe, we expressed ChR2 in STN neurons using retrograde viral transduction in vglut2-Cre mice (Figure 5 A, see methods).…”
Section: Resultsmentioning
confidence: 99%
“…The STN is reciprocally connected to the GPe and has been considered to be the main source of excitatory input to the GPe (Kita et al, 1983; Kita and Kitai, 1991; Pamukcu et al, 2020). To study the STN inputs to GPe, we expressed ChR2 in STN neurons using retrograde viral transduction in vglut2-Cre mice (Figure 5 A, see methods).…”
Section: Resultsmentioning
confidence: 99%
“…To allow for optogenetic manipulations, fiber optic cannulae were implanted bilaterally at the region of interest (Pamukcu et al, 2020) three weeks after stereotaxic injections. Each fiber cannula was assembled with an optical fiber (0.66 NA, 250 µm core) (Prizmatix) secured into a zirconia ferrule (1.25 mm O.D.)…”
Section: Stereotaxic Injections and Fiber Implantationsmentioning
confidence: 99%
“…Our previous studies established that PV + neurons and Npas1 + neurons play causal, but opposite roles in regulating locomotion-PV + neurons are movement-promoting and Npas1 + neurons are movement-suppressing (Glajch et al, 2016;Pamukcu et al, 2020). Consistent with our earlier observations, our analysis here showed that mice exhibited more mobile behavior (i.e., locomotion) when PV + neurons were optogenetically stimulated and more immobile behavior (i.e., fine movement and motionless) when Npas1 + neurons were optogenetically stimulated.…”
Section: Markerless Tracking Effectively Extracts Behavioral Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the GPe contains a heterogenous population of neurons (Hernandez et al, 2015;Hegeman et al, 2016;Saunders et al, 2018;Abecassis et al, 2020;Cherian et al, 2020), the identity of neurons that receive dSPN input remains elusive. As we have established PV + neurons and Npas1 + neurons in the GPe have distinct circuit and functional roles (Cherian et al, 2020;Pamukcu et al, 2020), we hypothesized that dSPNs regulate motor output by targeting a select subset of these neurons. Here, using transgenic and molecular tools, we dissected the cellular and spatial organization of the striatopallidal system; using in vivo optogenetics and machine-learning approaches, we studied the behavioral relevance of the striatopallidal subcircuits.…”
Section: Introduction (286 Words)mentioning
confidence: 95%